Meningkatkan Kaeaktifan Belajar Siswa Menggunakan Model Pembelajaran Project Based Learning untuk Siswa Kelas IV Sekolah Dasar - Rizki Permatahati, Diyan; Yusi R, Listik; Anas Wahyuni, Esti (LP2M, Institut Agama Islam Qamarul Huda, 2024)
This research was designed with the aim of increasing the learning activity of class IV students at SDN Kedondong by implementing a project based learning model. The type of research used is classroom action research (PTK) which adopts the spiral model from C. Kemmis and Mc. Taggart, with implementation in 2 cycles. Each cycle consists of four stages, namely planning, implementing actions, observing and reflecting. The data analysis technique in this research uses quantitative descriptive analysis techniques obtained from primary data during the research. Primary data comes from observations while in the field while secondary data is obtained from documents of learning activities in previous lessons. The results of the study showed an increase in the level of score completion in learning activity as measured by KKM ≥ 75 between pre-cycle, cycle 1 and cycle 2, amounting to 42.10%: 73.68%: 84.21%. From the research results, it can be concluded that the application of project-based learning has been proven to be able to increase the learning activity of class IV students at SDN Kedondong.